The Perspectives of Legal Practitioners on the Concept and Categories of Third Parties in the Household under Islamic Family Law in Malaysia - Ismail, Nurbazla; Mohamad, Abdul Basir (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Islamic Family Law in Malaysia provides an interpretation for divorce including punishment for factors that cause divorce, especially for certain groups. However, the factor discussed in this study is the involvement of a third party in the household. Questions arise regarding the term ‘third party in the household’ and how to categorise this third party. Therefore, this study aims to clarify the definition and categorisation of the third party in the household. This study uses a qualitative approach that collects data using document analysis methods and semi-structured interviews taken in three Syariah Courts located in the states of Selangor, Kelantan, and Terengganu. The results of the study are analysed using descriptive and thematic methods. Based on the interview findings, this study reveals that there is no specific interpretation of the term ‘third party in the household.’ A third party in a household is defined by the role they play in association with the household. As for the categorisation of the third party, two categories are identified: parents/in-laws/siblings and society/strangers/outsiders. This study provides significant implications to legal practitioners and researchers regarding the term ‘third party in the household’ that can be used to uphold justice in cases involving divorce.